2018
DOI: 10.1002/acn3.569
|View full text |Cite
|
Sign up to set email alerts
|

Rho‐kinase inhibitors do not expand hematoma volume in acute experimental intracerebral hemorrhage

Abstract: Rho‐associated kinase (ROCK) is an emerging target in acute ischemic stroke. Early pre‐hospital treatment with ROCK inhibitors may improve their efficacy, but their antithrombotic effects raise safety concerns in hemorrhagic stroke, precluding use prior to neuroimaging. Therefore, we tested whether ROCK inhibition affects the bleeding times, and worsens hematoma volume in a model of intracerebral hemorrhage (ICH) induced by intrastriatal collagenase injection in mice. Tail bleeding time was measured 1 h after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Additional inhibition by ROCK2-selective inhibitor can further reduce total ROCK activity and promotes the adipogenic differentiation toward to beige adipocytes ( Figure 8A). Indeed, its therapeutic potential has been explored in fibrotic disease, 15 focal cerebral ischemia, 16,61,62 and auto-immune disease. 15 Because the hypotensive phenotype that commonly occurred with ROCK pan-inhibitors was not observed when KD025 tested in systemic application, 16 it has been emerging as an important breakthrough in systemic application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional inhibition by ROCK2-selective inhibitor can further reduce total ROCK activity and promotes the adipogenic differentiation toward to beige adipocytes ( Figure 8A). Indeed, its therapeutic potential has been explored in fibrotic disease, 15 focal cerebral ischemia, 16,61,62 and auto-immune disease. 15 Because the hypotensive phenotype that commonly occurred with ROCK pan-inhibitors was not observed when KD025 tested in systemic application, 16 it has been emerging as an important breakthrough in systemic application.…”
Section: Discussionmentioning
confidence: 99%
“…15 Because the hypotensive phenotype that commonly occurred with ROCK pan-inhibitors was not observed when KD025 tested in systemic application, 16 it has been emerging as an important breakthrough in systemic application. Indeed, its therapeutic potential has been explored in fibrotic disease, 15 focal cerebral ischemia, 16,61,62 and auto-immune disease. 17,[63][64][65][66] In addition to the pro-beige adipogenic action of KD025, we have noticed an anti-adipogenic action of KD025 as reflected by reduced perilipin levels in the drug-treated SV cells ( Figure 7D, 7).…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies, administration of fasudil or ROCK2 specific inhibitor KD025, did not affect the neurological outcome or the size of hematoma after ICH (Akhter et al, 2018). It is noteworthy to mention that KD025 was less potent than fasudil in stopping intracerebral bleeding, whereas it was more potent in reducing the hematoma size (Akhter et al, 2018). In another study, fasudil alone did not inhibit the RHOA activity, whereas pitavastatin attenuated RHOA activation in VSMCs following SAH (Naraoka et al, 2013).…”
Section: Implication In Hemorrhagic Stroke Therapymentioning
confidence: 97%
“…Recent clinical studies have reported a slight improvement in the clinical outcomes of patients treated with the ROCK inhibitor fasudil 24 h following hemorrhagic stroke onset ( Zhao et al, 2011 , 2006 ). In experimental studies, administration of fasudil or ROCK2 specific inhibitor KD025, did not affect the neurological outcome or the size of hematoma after ICH ( Akhter et al, 2018 ). It is noteworthy to mention that KD025 was less potent than fasudil in stopping intracerebral bleeding, whereas it was more potent in reducing the hematoma size ( Akhter et al, 2018 ).…”
Section: The Wnt Pathway In Hemorrhagic Strokementioning
confidence: 99%
“…The specific disruption of each ROCK isoform by gene targeting in mice, using short interfering RNA (siRNA)-based gene silencing in cells and CRISPR gene editing provides growing evidence of distinct cellular, physiological and pathophysiological functions of the two isoforms. Introduction of KD025, the first highly selective ROCK2-isoform inhibitor (Boerma et al 2008 ), allows novel exploration of its therapeutic potential in various vascular, immune and neuronal disorders (Akhter et al 2018 ; Boerma et al 2008 ; Flynn et al 2016 ; Lee et al 2014 ; Sadeghian et al 2018 ; Sharma and Roy 2020 ; Weiss et al 2016 ; Zanin-Zhorov et al 2014 , 2016 , 2017 ). In this review, we will summarize the milestone discoveries in ROCK research and the current understanding of ROCK signaling in embryonic development, update current discoveries from knockout and knockin mouse models, and stem cell research.…”
Section: Introductionmentioning
confidence: 99%